PAX-9 mutation of Non-Syndromic Hypodontia in Three Malaysian Families - Lestari, Widya; Ardini, Yunita Dewi; Mohamaed Idrus, Nur Farahlyah; Rosley, Nur Syahirah (2021)
This poster was submitted to 38th Asia Pacific Dental Congress, Hongkong 17-19 June 2016